Arduino-Based Real-Time Drone Performance Monitoring with MEMS Sensor Application - Jaaffar, Megat Najmudin; Che Soh, Mohd Jais (Evolution in Electrical and Electronic Engineering, 2025)
This paper presents the design and implementation of a real-time drone performance monitoring system using MEMS sensor applications. The system employs MPU6050 gyroscope and accelerometer modules to collect key parameters such as orientation and stability. It also integrates voltage and current sensors (SIMPLE B25, ACS712, INA219) for energy monitoring. Data are processed via Arduino UNO and ESP32 microcontrollers and displayed using Arduino IDE and ThingSpeak cloud. This setup enables real-time tracking and enhances operational efficiency, making it suitable for applications like autonomous navigation and aerial surveillance. Results obtained shows the prototype operated efficiently and works as intended. In conclusion, the proposed system demonstrates the ability of MEMS sensors working in tight structure of a drone.